Parallel [TG(GA)3]n-homoduplexes/thioflavin T: an intense and stable fluorescent indicator for label-free biosensing. Issue 1 (21st November 2019) - Liu, Qiang; Jing, Shaochun; Liu, Mei; Jin, Yan; Li, Baoxin
Abstract : Compared with the G-quadruplex/ThT fluorescent system, parallel [TG(GA)3 ] n -dsDNA/ThT is a stable and strong fluorescent indicator for label-free biosensing. Abstract : Different from the classical antiparallel DNA double-stranded structure, parallel DNA duplexes possess unique structures and potential biological functions. In this work, we found that the parallel DNA homoduplex from the [TG(GA)3 ] n sequence ([TG(GA)3 ] n -dsDNA) can dramatically enhance the fluorescence of thioflavin T (ThT), and the fluorescence enhancement is proportional to the number ( n ) of TG(GA)3 units in [TG(GA)3 ] n . Compared with the traditional G-quadruplex/ThT system, [TG(GA)3 ] n /ThT showed more stable and stronger fluorescence emission. In addition, coupled with an isothermal exponential amplification reaction, [TG(GA)3 ]3 /ThT was used as a label-free fluorescent probe to detect microRNA, and the [TG(GA)3 ]3 /ThT probe exhibited higher sensitivity than the G-quadruplex/ThT probe. This work provides a new paradigm to design label-free fluorescent biosensing/imaging systems.